2017
DOI: 10.1038/s41598-017-11597-z
|View full text |Cite
|
Sign up to set email alerts
|

MALDI-TOF-MS based identification and molecular characterization of food associated methicillin-resistant Staphylococcus aureus

Abstract: Food-borne methicillin resistant Staphylococcus aureus (MRSA) is involved in two-fold higher mortality rate compared to methicillin susceptible S. aureus (MSSA). Eventhough Mysuru recognized as cleanest city in the world, prevalence of food contamination is not detailed. The aim is to screen food samples from Mysuru area and to characterize MRSA strain, employing MALDI-Biotyper, multiplex PCR to distinguish between MRSA and MSSA by PCR-coupled single strand conformation polymorphism (PCR-SSCP). Of all the food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 54 publications
3
36
0
1
Order By: Relevance
“…Therefore, the first step would be, as it was already done for some bacteria (Manukumar and Umesha, 2017), to detect specific peaks associated with the resistance or the susceptibility to an antifungal drug (Posteraro et al, 2013). This aim is promising since typing with MALDI-TOF MS was shown to be able to cluster C. glabrata isolates according to their fluconazole susceptibility profile (Dhieb et al, 2015) but no resistance nor susceptibility peaks has yet been identified.…”
Section: Maldi-tof and Antifungal Resistance Detectionmentioning
confidence: 99%
“…Therefore, the first step would be, as it was already done for some bacteria (Manukumar and Umesha, 2017), to detect specific peaks associated with the resistance or the susceptibility to an antifungal drug (Posteraro et al, 2013). This aim is promising since typing with MALDI-TOF MS was shown to be able to cluster C. glabrata isolates according to their fluconazole susceptibility profile (Dhieb et al, 2015) but no resistance nor susceptibility peaks has yet been identified.…”
Section: Maldi-tof and Antifungal Resistance Detectionmentioning
confidence: 99%
“…Protein A typing ( spa typing) is an inexpensive method, which is based on the sequence analysis of variable number tandem repeats (VNTRs) in the encoding gene of this protein ( spa ), while also taking the number of repeat variations and point mutations into account (e.g., t011, t899) [118,119,120]. As a novelty, some studies have reported in the use of MALDI-TOF MS for the rapid discrimination of epidemic clones of MRSA, based on the association of their measured protein peaks (for an excellent review on the background of mass spectrometry, see [121]) and their spa types [118,122]. Whole-genome sequencing (WGS) is currently considered to be the gold standard as a molecular typing tool for the investigation of MRSA outbreaks [123].…”
Section: Genetics Of Mrsa Typing Methodsmentioning
confidence: 99%
“…It is based on examining the protein profile of the isolate, and it creates a 'fingerprint' unique for a given species. Furthermore, it is simple to execute and is automated [27][28][29][30]. Moreover, its use significantly shortens the time of identification of the tested microorganism -after bacteria isolation and preparation of sample, only a few minutes are needed for examination [27,29].…”
Section: Protein Profiling By Matrix-assisted Laser Desorption/ionizamentioning
confidence: 99%
“…The minimum number of bacterial cells necessary for correct identification of a species is about 10 5 [27]. Additionally, it was noticed that the concentration of bacterial cells in the sample significantly influences the efficiency of the method [28].…”
Section: Protein Profiling By Matrix-assisted Laser Desorption/ionizamentioning
confidence: 99%